Perspectives on neuropsychology and clinical care in paediatric and adolescent medicine. (July 2020) - Griffin, Angela; Deeba, Farah; Dennison, Taryn; Moore, Anna
As a child and adolescent neuropsychology service based within a paediatric psychology team at a large teaching hospital, we meet children and young people across the age range who experience cognitive impairment as a result of long-term health conditions or traumatic brain injury. We have a remit of providing a neuropsychological assessment and report. Typically, a neuropsychology report includes recommendations for home and for school. However, research suggests that their uptake is variable and depends on the understanding and resources of families and school systems. As a stretched service, we have very limited capacity to follow the work through to the extent that we might like. Therefore, we are always seeking effective ways to support the ongoing adaptation and implementation of the assessment recommendations in the child's various day-to-day contexts. We address both the cognitive functioning and the psychological well-being of the child as a unified whole. Drawing on systemic ideas influences our communications with children, families, schools and the medical teams in ways which help bridge the gap between hospital-based assessment and everyday life. This article describes how we are integrating our systemic and neurodevelopmental perspectives to make the assessment and the findings a meaningful intervention in themselves. We consider ways of sharing neuropsychology findings which promote the child's psychological well-being in their different contexts: hospital, home, school, community and culture.